Assessing the Chronology and Rewrapping of Funerary Bundles at the Prehispanic Religious Center of Pachacamac, Peru. Issue 3 (September 2014) - Takigami, Mai K.; Shimada, Izumi; Segura, Rafael; Muno, Sarah; Matsuzaki, Hiroyuki; Tokanai, Fuyuki; Kato, Kazuhiro; Mukai, Hitoshi; Takayuki, Omori; Yoneda, Minoru
Abstract : Over 30 funerary bundles were excavated in 2005 from a large chamber tomb at the prehispanic religious center of Pachacamac on the central coast of Peru. The largest and most elaborate bundle was found in the innermost part of the tomb, tightly surrounded by other bundles. We hypothesized that this bundle contained the deceased leader of a social group whose members collectively cared for their ancestor's bundle (for example, by rewrapping it) and continued to use the tomb to inter deceased individuals from subsequent generations. We tested this hypothesis by dating samples from different layers of the wrapping materials and soft tissue from the bodies and conducting a Bayesian analysis of the resultant dates. We determined carbon and nitrogen isotope ratios in the diet of the interred individuals to correct for marine reservoir effects. Our findings suggest that (1) rewrapping did not occur; (2) the tomb was used for over 500 years starting at cal A.D. 1000; and (3) existing bundles were reshuffled each time new bundles were introduced. Overall, diverse lines of evidence indicate that the tomb had a complex use history and contained individuals with diverse geographical and social origins. This challenges conventional thinking about the social and chronological significance of coexisting bundles in large tombs.